2013
DOI: 10.1371/journal.pone.0081246
|View full text |Cite|
|
Sign up to set email alerts
|

Biodiversity Promotes Tree Growth during Succession in Subtropical Forest

Abstract: Losses of plant species diversity can affect ecosystem functioning, with decreased primary productivity being the most frequently reported effect in experimental plant assemblages, including tree plantations. Less is known about the role of biodiversity in natural ecosystems, including forests, despite their importance for global biogeochemical cycling and climate. In general, experimental manipulations of tree diversity will take decades to yield final results. To date, biodiversity effects in natural forests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 34 publications
14
117
1
1
Order By: Relevance
“…Drivers of primary productivity generally are correlated in nonexperimental studies of BEF relationships across natural landscapes (21)(22)(23). The individual contributions of these drivers thus are difficult to disentangle.…”
Section: Discussionmentioning
confidence: 99%
“…Drivers of primary productivity generally are correlated in nonexperimental studies of BEF relationships across natural landscapes (21)(22)(23). The individual contributions of these drivers thus are difficult to disentangle.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of NC as a driver of EF is heuristically compelling, ecologically reasonable, and supported by simulation models, experiments, and some observational studies (e.g., Tilman 1999;Cardinale et al 2007;Fargione et al 2007;Morin et al 2011). For instance, Barrufol et al (2013) found that tree species richness was positively related to biomass accumulation during tropical forest succession. Tree size inequality, which is related to tree species diversity, has been linked with increased biomass in boreal forests .…”
Section: Discussionmentioning
confidence: 99%
“…through competitive interactions, or vice versa [9]. This ambiguity can be resolved to some extent by comparative studies in which field plots spanning gradients in species richness but otherwise uniform site conditions are selected [10]. …”
Section: Introductionmentioning
confidence: 99%